Isolation of the left innominate artery: When to operate? - Samuel J. H. Parsons; Harry Nuttall; Alexander Jones (Wolters Kluwer Medknow Publications, 2024)
A right aortic arch with an isolated left innominate artery from the pulmonary artery is an exceedingly rare congenital cardiac malformation. We describe the management and complex surgical timing considerations in two such cases, successfully operated on day 4 and 7 months of age, including the use of cranial ultrasound as a helpful tool to guide decision-making. We also describe the first reported association of this defect with a 4q25 deletion encompassing the LEF1 gene.